2008
DOI: 10.1590/s0074-02762008000400002
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction genotyping of Epstein-Barr virus in scraping samples of the tongue lateral border in HIV-1 seropositive patients

Abstract: The Epstein-Barr virus (EBV) is the etiological agent of oral hairy leukoplakia (OHL), an oral lesion with important diagnostic and prognostic value in acquired immunodeficiency disease syndrome. The two EBV genotypes, EBV-1 and EBV-2, can be distinguished by divergent gene sequences encoding the EBNA-2, 3A, 3B, and 3C proteins. The purpose of this study was to identify the EBV genotype prevalent in 53 samples of scrapings from the lateral border of the tongue of HIV-1 seropositive patients, with and without O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
0
13
1
1
Order By: Relevance
“…In Australia, genotype B infections were reportedly six-fold higher in HIV-infected patients than in the general community [40]. Although we did not find any genotype B cases in our HIV-infected population (table 1), published data pertaining to EBV genotypes in HIV infection show conflicting results; studies report the dominance of genotype A [9,32], equal prevalence of both genotypes A and B [29], the occurrence of co-infections [40,43], or genotype switching over the course of infection [41]. These inconsistencies may perhaps be attributed to the immune dysregulation caused by HIV.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…In Australia, genotype B infections were reportedly six-fold higher in HIV-infected patients than in the general community [40]. Although we did not find any genotype B cases in our HIV-infected population (table 1), published data pertaining to EBV genotypes in HIV infection show conflicting results; studies report the dominance of genotype A [9,32], equal prevalence of both genotypes A and B [29], the occurrence of co-infections [40,43], or genotype switching over the course of infection [41]. These inconsistencies may perhaps be attributed to the immune dysregulation caused by HIV.…”
Section: Discussioncontrasting
confidence: 52%
“…This was expected, as genotype A is detected more frequently in Western and Asian countries [9,29]. Moreover, genotype A was isolated from all study groups and was not limited to a specific disease.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…3 EBV type 1 is prevalent in most of populations studied. 4,5 However, other studies have revealed that in specific geographic areas, the prevalence of EBV type 1 is similar to the prevalence of EBV type 2. 6 Risk factors for EBV infection and its genotypes have not been fully investigated.…”
Section: Introductionmentioning
confidence: 95%
“…Os dois tipos apresentam-se em diferentes localizações geográficas, o EBV-1 é predominante em países ocidentais, e o EBV-2 é prevalente na África, Oceania (Nova Guiné), e em pacientes HIV positivo. As propriedades biológicas desses 2 tipos são também distintas, o EBV-1 é mais potente do que o EBV-2 na transformação e imortalização de linfócitos B infectados in vitro, mais ambos os tipos de EBV podem atuar como patógenos humanos 3,10 . Muitos estudos têm demonstrado que a expressão de genes virais latentes, especialmente os genes EBNAs e LMP-1 (proteína de membrana latente-1), tem sido intimamente associado com infecção latente que se correlaciona com a imortalização e carcinogênese 11 .…”
Section: Epstein-barr Vírusunclassified